Dynamics of Self Control in Single Mother : A Case Study - Lailatul Badriah; Siti Khorriyatul Khotimah; Lufiana Hanany Utami (International Conference on Sustainable Health Promotion, 2025)
Self control is an individual’s ability to regulate behavior, emotions, and thoughts to achieve goals, especially in challenging situations. This study aims to describe the dynamics of self-control in a 56-year-old single mother of six, wich is five of whom successfully completed college, and the factors influencing her self-control. The method used was a qualitative case study design involving one participant who met the inclusion criteria. The data were collected through interviews and documentation, then analyzed using content analysis techniques. The results indicate that participants developed self-control strategies that included behavioral control, cognitive control, decision-making, information seeking, and reflection on past experiences. Influencing factors included family support, social activities, and high religiosity. These findings emphasize the importance of self-control in facing daily challenges for single mothers.